TRANSFORMASI PEMBELAJARAN EKSTRAKURIKULER ROBOTIKA dalam PEMBERDAYAAN KREATIVITAS DAN LOGIKA ANAK SEKOLAH DASAR DI SDN MARGOREJO 1 SURABAYA - Kridoyono, agung (Universitas Nahdlatul Ulama Sidoarjo, 2025)
Strengthening practical 21st century skills, such as creativity, logical thinking and problem solving, needs to be instilled from an early age to form a generation of learners who are adaptive to technological developments. This community service activity aims to introduce and implement robotics learning to grade 5 students at SDN Margorejo 1 Surabaya as part of an extracurricular program. The program was implemented for two months in the form of weekly workshops which included an introduction to basic robotics concepts, practice assembling line follower robots, as well as child-friendly, visual-based programming logic simulations. The implementation method uses an active-participatory approach through reflection, interactive discussions and direct practice in groups. Evaluation is carried out through qualitative observations and measuring students' enthusiasm and involvement in completing robotics challenges. The results of the activities showed a significant increase in students' interest in learning, logical thinking abilities, and creativity. Responses from teachers and parents also show that this activity is relevant and worthy of adoption as a form of innovative learning at the elementary school level. This program provides evidence that robotics learning can be an effective medium for fostering critical and collaborative thinking skills from an early age. Keywords: robotics creativity, programming logic, elementary school, community service, educational workshops